THE SUCCESS OF CALLIGRAPHY LEARNING ON MAHARAH AL-KITABAH OF AL-QU'RAN MEMORIZERS AT MADRASAH ALIYAH MA'HAD TAHFIZHIL QUR'AN FOUNDATION ISLAMIC CENTER NORTH SUMATERA - Jaalna Baeha; Lily Sardiani Daulay (Jurnal Eduslamic, 2024)
The Qur'an is one of the revelations of Allah SWT revealed to the Prophet Muhammad SAW and is a guide for Muslims. The AL-Qur'an is full of meanings that are very related to life, also the discussion in the AL-Qur'an is relevant to the times. The SU Islamic Center Foundation is one of the modern-based boarding schools that has produced thousands of memorizers of the Qur'an. However, there are difficulties for male students and female students in writing Arabic letters, and the Qur'an contains Arabic writing. This research aims to find a comprehensive understanding according to the title under study. This research methodology is a type of qualitative descriptive method, namely literature study by looking for references from journals and theses that are appropriate regarding the effectiveness of calligraphy on maharah al-kitabah (calligraphy) of memorizing the Qur'an. In terms of analyzing data, researchers use data collection techniques, namely through observation, direct interviews with resource parties at Ma'had Tahfizhil Qur'an Islamic Center SU Foundation and documentation. The results of the study show that male students or female students do not all have a high interest in learning maharah al-kitabah (calligraphy), especially at the Madrasah Aliyah level, and also lack of skills in writing.